2021
DOI: 10.21037/gs-20-657
|View full text |Cite
|
Sign up to set email alerts
|

Medical professionals’ knowledge of the use of external breast prostheses among breast cancer patients in China—a cross-sectional study

Abstract: Background: Breast loss has a negative effect on women physically, psychologically and socially. External breast prostheses can improve patients' figure physically, increase their self-confidence, and thus improve quality of life. Little is known about the knowledge of medical professionals on the use of external breast prostheses in mainland China. This study sought to examine medical professionals' knowledge of the use of external breast prostheses among breast cancer patients in China.Methods: Self-designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, over time, they may have experienced many changes in their bodies and ended up unhappy with their BI. Furthermore, the mastectomy and MRM patients have a xed scar in their breast area post-surgery, and may have found that they can had alternatives such as external (prosthesis) [2,26,53] to keep their BI stable and didn't have any worries about further recurrent or post-surgical complications. However, one study examined changes in BI and QoL in women who underwent BCS compared with mastectomies and found similar uctuation in BI after BCS, but that study did not include BR patients [65].…”
Section: Discussionmentioning
confidence: 99%
“…However, over time, they may have experienced many changes in their bodies and ended up unhappy with their BI. Furthermore, the mastectomy and MRM patients have a xed scar in their breast area post-surgery, and may have found that they can had alternatives such as external (prosthesis) [2,26,53] to keep their BI stable and didn't have any worries about further recurrent or post-surgical complications. However, one study examined changes in BI and QoL in women who underwent BCS compared with mastectomies and found similar uctuation in BI after BCS, but that study did not include BR patients [65].…”
Section: Discussionmentioning
confidence: 99%
“…Breast lumps without pain were most common, followed by breast lumps with pain, constituting 62.4% to 98% of the initial symptoms reported. 17,19,24,25,27,31 Li's 19 quantitative analysis showed that women having breast symptoms without pain, bleeding, or discharge were more likely to have longer patient intervals than An et al women having these symptoms. The qualitative studies consistently reported that some women thought that a breast lump was not serious as long as it was painless, 23,29 and the absence of physical discomfort led women to think "they would be fine" 18(p400) and dismiss their symptoms.…”
Section: Symptom Appraisalmentioning
confidence: 99%
“…The quality scores of studies conducted in mainland China ranged from 20 to 35, whereas those conducted in Taiwan and Hong Kong generally showed higher quality, scoring from 28 to 40 and 29 to 39, respectively. Also, the quality of the studies published in Chinese was relatively low (20)(21)(22)(23)(24)(25)(26)(27)(28), compared with the quality of those published in English (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Because this review was integrative, no cutoff score was used to exclude studies.…”
Section: Study Qualitymentioning
confidence: 99%
See 2 more Smart Citations